Proses Pengolahan dan Pemasaran Keripik Tempe di Desa Gundik - Fathin Nada; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2023)
A Tempe-making businesses in Village are mostly carried out in home industries or home industries. this research, the aim is to find out the Marketing Improvement of Tempe Chips in Gundik Secaa Village Online & Offline. This community service uses the ABCD (Asset-Based Community Development) approach, which is an approach in community service by seeing and knowing the strengths and assets that exist to create an empowered community. The marketing of tempe chips Mr. Miswanto & Mrs. Suyatmi underwent a slight change, starting to promote this product by entrusting it to shops so that now consumers can directly buy at home (Offline) or order via online. Based on Mandiri's asset identification, this tempe chip product still requires innovation both in terms of product and marketing to maintain product quality.